Psychological Capital dan Workplace Well-Being sebagai Prediktor bagi Employee Engagement - Elisa Kurniadewi (UIN Sunan Kalijaga, 2016)
In order to be a successful organization it is necessary to optimize the potentials of its human resources. It is including attention to factors that may be predictors for employee engagement. The study was conducted to determine whether variables of psychological capital and workplace well-being can be a predictor for employee engagement. The respondents in this study are 202 people which come from two government institutions of X. The conducted data ware analyzed by using the structural method and with the help of LISREL 8.70. The results showed: (1) Psychological capital influence the employee engagement positively, but it is not significant. (2) Workplace well-being influences the employee engagement positively and significantly with standardized value of 0.62 and t-value of 4.52. (3) Psychological capital and Workplace well-being proved influence the employee engagement. However psychological capital is not influence significantly to the employee engagement (because the standardized value of 0:23, with a value of t-1.77 does not meet the minimum requirements of direct significance value which is t-1.96). While workplace well-being influences positively and significantly to the employee engagement (with standardized value of 0.62 and t-value of 4.52) and it can be used to predict the employee engagement. Thus, workplace well-being with (1) the extrinsic dimension which consists of: using time as well as possible, working conditions, supervision, promotion and salaries, and (2) intrinsic dimension which consists of: job responsibility, the meaning of employment, self employment, the use of skills and knowledge to work as well as a feeling of achievement in work - it is well proved to be factors in predicting employee engagement.